Crystal c-axes (fabric analyser G50) of ice core samples (vertical thin sections) collected from the polar ice core EGRIP, 111-2651 m depth - Ilka Weikusat; Nicolas Stoll; Jan Eichler; Johanna Kerch; Ina Kleitz; Daniela Jansen; Wataru Shigeyama; Tomoyuki Homma; Maddalena Bayer; Pia Götz; Ernst-Jan N Kuiper; Julien Westhoff; et al. (PANGAEA, 2025)
Polarisation microscopy image data from vertical thin sections from the EGRIP ice core were acquired with a Fabric Analyser (G50, Russell-Head Instruments). 1152 sections from 225 bags were measured in the field camp at EGRIP, Greenland, during field seasons 2017, 2018, 2019, 2022, and 2023. A bag refers to an ice core segment of 55 cm length which is typically cut into six pieces of 9 cm length from which thin sections (approx. 250-300 μm thick, max. 7x9 cm^2) are prepared using a manual sledge microtome. The majority of bags are continuously sampled with up to six adjacent samples with a bag interval of approx. 10 +- 6 m. Up to three parallel and/or orthogonal vertical sections were prepared only from ice core volume samples (75% of ice core from bottom of approx. every 200th bag, corresponding to depth of 6th sample in bag). Sample folders are named according to the convention EGRIP<bag>\_ -<cut>\_<additional-info>. Data are not available between 2121 and 2417 m. Each section folders contains a manually prepared mask image (background.bmp) in preparation for image processing to exclude image artefacts from the sample margins. The resolution of the image data is 500 px/cm. Quality images are provided by the instrument as well as images showing crystal c-axis orientation per pixel. The binary file (data.cis) contains all relevant information to evaluate the section with regard to the crystal-preferred orientation (CPO) of the ice thin sections.
In: Weikusat, Ilka; Stoll, Nicolas; Kerch, Johanna; Eichler, Jan; Jansen, Daniela; Darányi, Kyra; Kleitz, Ina; Shigeyama, Wataru; Homma, Tomoyuki; Bayer, Maddalena; Götz, Pia; Kuiper, Ernst-Jan N; Saruya, Tomotaka; Franke, Steven; Hellmann, Sebastian; Rathmann, Nicholas Mossor; Wallis, David; Cook, Eliza; Kipfstuhl, Sepp (2025): Crystal-preferred orientation data from the polar ice core EGRIP (vertical and horizontal thin section data, raw and processed), 111-2664 m depth, 2017 - 2023 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.983953